Development of a Rigid Polyurethane Foam-Reinforced Resilient Masonry Wall System - Forsythe, Carly M. (My University, 2012)
Unreinforced masonry (URM) constitutes a large part of current building inventory worldwide, and this type of construction also represents a major seismic risk, especially in developing countries where URM is widely used. During an earthquake, URM walls are unable to dissipate seismic forces without experiencing considerable damage or collapse. Due to their lack of ductility, URM walls fail in a brittle manner, which can leads to damaged face shells becoming falling debris and a major source of hazard. The aim of this study is to investigate the applicability of using polyurethane foams as an inexpensive reinforcement technique for both retrofitting existing and new URM construction.
Experimental testing of the reinforced masonry walls showed a large increase in the resiliency of the wall, with an increase in the out-of-plane capacity of up to 34 times over the URM specimen, and with the addition of rope reinforcement an increase in the out-of-plane capacity of up to 90 times the URM specimen was achieved. This system allows walls to experience a considerable amount of deflection before ultimate failure is reached. Within certain limits, the polyurethane foam is able to demonstrate elastic characteristics. By developing foam with higher densities, higher compressive, tensile, flexural and shear strengths can be reached. This type of reinforcement allows for less damage during low seismic events, and through the greater resiliency of the system, walls are able to remain stable and exhibit post-peak strength during a stronger seismic event. In its ultimate limit state, the wall will fail, however collapse is typically prevented – reducing the amount of hazardous debris and saving the lives of the buildings occupants.
Keywords: unreinforced masonry; polyurethane foam; out of plane; seismic; Structural Engineering; Structural Engineering